Relationships between cognition and literacy in children with attention‐deficit/hyperactivity disorder: A systematic review and meta‐analysis. (4th October 2021) - McDougal, Emily; Gracie, Hannah; Oldridge, Jessica; Stewart, Tracy M.; Booth, Josephine N.; Rhodes, Sinéad M.
Abstract : Evidence suggests that cognitive and literacy difficulties are common for children with Attention‐Deficit/Hyperactivity Disorder (ADHD). The current systematic review and meta‐analysis investigated the relationship between cognition and literacy in children with ADHD. Ten thousand and thirty‐eight articles were screened against the inclusion criteria and six eligible studies were retained for final review. Where two or more studies used comparable measures of cognition and literacy, a meta‐analysis of the relationship between these measures was undertaken. A narrative synthesis of all included studies was also completed. There were medium effect sizes between working memory and aspects of reading, and small effect sizes between processing speed and reading. Inhibition and attention had differential relationships with aspects of literacy with varying effect sizes. This systematic review demonstrates differential relationships between aspects of literacy and cognition in children with ADHD. Further examination of these relationships is warranted to support intervention development.